Studies on Brazilian Pseudophasmatidae (Phasmatodea) with the description of a new species of Agrostia Redtenbacher and new records for Metriophasma Uvarov and Parastratocles Redtenbacher - Heleodoro, Raphael Aquino; Mendes, Diego Matheus de Mello; Rafael, José Albertino (Revista Brasileira de Entomologia, 2017)
Pseudophasmatidae currently includes 65 species recorded from Brazil. In this paper, we increase this number to 68 species by describing Agrostia flavimaculata sp. nov., based on male and female specimens from Acre and Amazonas states. Furthermore, Parastratocles multilineatus (Rehn) and Metriophasma (Metriophasma) diocles (Westwood) are recorded for the first time from Brazil based on specimens from Rondônia, Acre and Amazonas states. A key to species of Agrostia is also given. © 2017 Sociedade Brasileira de Entomologia